Tokoh-Tokoh / Ulama Hadis Kontemporer (Dunia dan Indonesia) - Rahmatullah; Muhammad Yahya; Sitti Asiqah Usman Ali (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to examine the roles and contributions of contemporary hadith scholars, both from the international arena and Indonesia, in the development of hadith studies in the modern era. Using a qualitative research method with a library research approach, this study explores the biographies, scholarly works, and methodological approaches employed by these scholars in understanding and teaching hadith. Prominent figures such as Nasaruddin Al-Albani and Yusuf al-Qaradawi at the international level, as well as K.H. Hasyim Hasyari, Quraish Shihab, Syuhudi Ismail, Teungku Muhammad Hasbi al-Shiddieqy, and Kamaruddin Amin in Indonesia, are the primary focus of this research. Contemporary hadith scholars not only preserve the classical tradition of hadith scholarship but also offer new approaches that are relevant to current social and intellectual contexts. Their thoughts reflect efforts to integrate hadith texts with modern realities, promoting a more inclusive and contextual understanding of hadith. This study is expected to provide both academic and practical insights for the advancement of hadith studies and serve as a valuable reference in understanding the dynamics of contemporary Islamic scholarship